Criteria of resilience infrastructure in flood-prone areas in Kelantan : a pilot study / Ezzat Fahmi Ahmad, Ida Nianti Mohd Zin, and Kartina Alauddin - Ahmad, Ezzat Fahmi; Mohd Zin, Ida Nianti; Alauddin, Kartina (Universiti Teknologi MARA, Perak, 2020)
The resilience infrastructure systems can be described as capable of resisting, absorbing and recovering from flood effects in a timely and efficient manner. The resilience infrastructure systems can be achieved through the implementation of resilience criteria (i.e. robustness; resourcefulness; rapidity; and redundancy). The objective of this paper is to determine the most important resilience criteria to strengthen infrastructure systems in flood-prone areas in Kelantan. A cross-sectional survey was conducted among communities in flood-prone areas in Kelantan. A total of 23 criteria were analysed subjected to descriptive analysis. The results of the analysis showed that robustness is the most important criteria.